2020
DOI: 10.1136/bmjebm-2020-111432
|View full text |Cite
|
Sign up to set email alerts
|

Maternal caffeine consumption and pregnancy outcomes: a narrative review with implications for advice to mothers and mothers-to-be

Abstract: ObjectivesCaffeine is a habit-forming substance consumed daily by the majority of pregnant women. Accordingly, it is important that women receive sound evidence-based advice about potential caffeine-related harm. This narrative review examines evidence of association between maternal caffeine consumption and negative pregnancy outcomes, and assesses whether current health advice concerning maternal caffeine consumption is soundly based.MethodsDatabase searches using terms linking caffeine and caffeinated bever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 111 publications
(161 reference statements)
1
38
4
3
Order By: Relevance
“…While some studies have found that high caffeine intake during pregnancy increases the risk of LBW [6,7,9] other studies did not nd a signi cant association [10,19,26]. This discrepancy might be due to differences in study populations, sample size, study design, and handling of potentially confounding variables.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…While some studies have found that high caffeine intake during pregnancy increases the risk of LBW [6,7,9] other studies did not nd a signi cant association [10,19,26]. This discrepancy might be due to differences in study populations, sample size, study design, and handling of potentially confounding variables.…”
Section: Discussionmentioning
confidence: 91%
“…Caffeine can also pass through all biological membranes and freely crosses the blood-brain barrier, and the placenta in pregnant women. Maternal and fetal plasma can attain equilibrium [9]. The immature fetal liver enzyme is not capable to metabolize it, ensuing in the accumulation of caffeine in the fetus this can increase the concentration of cellular cyclic adenosine mono phosphate (cAMP), interfering in fetal cell growth and development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the consumption of three or more coffees per day was associated with increased risk of low birth weight by around twofold, which was in alignment with previous studies using the Osaka Maternal and Child Health Study (OMCHS) prospective cohort, where maternal caffeine intake was associated with a 1.28 times increased risk of preterm birth per 100 mg/d of caffeine [ 27 ]. There are frequent reports of significant dose-response associations between coffee consumption and adverse birth outcomes, implying that “moderate” caffeine consumption during pregnancy as advised by healthcare professionals may not be safe [ 28 ]. As expected, compared to babies with no prenatal secondhand smoke exposure, babies with prenatal secondhand smoke exposure had increased risk of low birth weight, as did babies born to mothers who dieted during their pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, the maximum limit of caffeine intake recommended should be 200 mg/day [8,9]. Findings from observational studies and meta-analyses indicate that maternal caffeine consumption is reliably associated with miscarriage, stillbirth, low birth weight and/or small for gestational age, childhood acute leukemia and childhood overweight and obesity [10,11]. Recently, it has been associated in Korean pregnant women a higher risk of bleeding in early pregnancy among those with heavy coffee consumption (2 cups of coffee/day) before pregnancy [12].…”
Section: Introductionmentioning
confidence: 99%